Human Rights Performance Disclosure by Companies with Operations in High Risk Countries: Evidence from the Australian Minerals Sector. Issue 1 (20th October 2016) - Islam, Muhammad Azizul; Haque, Shamima; Roberts, Robin
Abstract : The aim of this study is to explore whether Australian mineral companies operating in high human rights risk countries provide more human rights disclosures than companies operating in low risk countries. A content analysis instrument containing 88 specific human rights performance items derived from a number of international human rights guidelines has been developed to investigate the annual reports, social responsibility reports and corporate websites of the top 50 Australian mineral companies (2010/2011). The findings show that human rights performance disclosures by companies with operations in high human rights risk countries are significantly higher than companies with operations in low risk countries. By disclosing extended human rights performance information, companies operating in high risk countries appear to ease community concerns about human rights violations. The finding is consistent with legitimacy theory, which posits that organisations respond to community concerns in relation to particular social issues. Abstract : Based on a content analysis of annual reports, social responsibility reports and corporate websites of the top 50 Australian mineral companies (2010/2011), this study shows that human rights performance disclosures by companies with operations in high human rights risk countries are significantly higher than companies with operations in low risk countries. The finding is consistent with legitimacy theory.